1969
DOI: 10.1021/j100844a041
|View full text |Cite
|
Sign up to set email alerts
|

Study of ion-solvent interaction of some tetraalkylammonium and common ions in N-methylacetamide from apparent molal volume data

Abstract: The apparent molal volumes, s, of six tetraalkylammonium iodides, namely, Et4NI to Hep4NI, have been determined in N-methylacetamide (NMA), at different temperatures and concentrations from which the limiting apparent molal volumes, ,°s, have been obtained for these salts. The results indicate that the vs. -\/c curves are almost straight lines for all the salts in the concentration range studied here. The curves for Et4NI and Pr4NI salts have a positive slope, and those for Bu4NI, Pen4NI, Hex4NI, and Hep4NI ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

1973
1973
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 3 publications
3
27
0
Order By: Relevance
“…On the other hand, the slope, S v shows that the ionion interactions. In generally, S v is positive, but it can be negative for some electrolytes; particularly for tetraalkylammonium salts [52][53][54], and also have been observed in this work, values of V m 1 , S v and B v for the ILs + DMSO systems were obtained at various temperatures by a linear regression analysis, and the results are listed in Table 4 along with their the standard deviations. It was found that the apparent molar volumes at infinite dilution, V m 1 for the ILs increase with the increase in the methyl group in the cation/ anion part of ILs at a particular temperature.…”
Section: Apparent Molar Volumessupporting
confidence: 67%
See 1 more Smart Citation
“…On the other hand, the slope, S v shows that the ionion interactions. In generally, S v is positive, but it can be negative for some electrolytes; particularly for tetraalkylammonium salts [52][53][54], and also have been observed in this work, values of V m 1 , S v and B v for the ILs + DMSO systems were obtained at various temperatures by a linear regression analysis, and the results are listed in Table 4 along with their the standard deviations. It was found that the apparent molar volumes at infinite dilution, V m 1 for the ILs increase with the increase in the methyl group in the cation/ anion part of ILs at a particular temperature.…”
Section: Apparent Molar Volumessupporting
confidence: 67%
“…The k s (solvent intrinsic) is the isentropic compression due to the compression of solvent molecules (DMSO), while k s (solute intrinsic) is the isentropic compression due to the compression of the hydration shell of ions or penetration of solvent molecules into the ILs [52].…”
Section: Apparent Molar Isentropic Compressionmentioning
confidence: 99%
“…They found that four water molecules are tightly associated with the organic cation, in addition to several more distant and more loosely associated water molecules. Gopal and Siddiqi suggested from partial molar volume measurements that Me 4 N + , Et 4 N + and Pr 4 N + are specifically solvated in N-methylacetamide, but that larger ions are not [15]. Gill reported that the apparent ionic radius of Me 4 N + ion in a variety of solvents is larger than its crystallographic radius, which would be consistent with it bearing a solvent shell [16].…”
Section: Introductionmentioning
confidence: 99%
“…In pure FA, the DHLL slope S v at 298.15 K is 1.104 calculated by Dunn [19] from experimentally determined ∂ ln ε/∂P data (ε, dielectric constant; P , pressure) according to the Redlich equation. However negative S * v has been found for a number of electrolytes in FA and in different other solvents [18,[20][21][22][23] as well as in aqueous solutions. Going from higher to lower compositions, there is a change in the sequence of φ V curves, after 25% in EG/W and after 75% in FA/W.…”
Section: Resultsmentioning
confidence: 99%